A simple potentiometric titration method for estimation of maleic anhydride in high molecular weight styrene-maleic anhydride copolymer. (February 2018) - Kate, Abhijeet S.; Basavaraju, K.C.
Abstract: A potentiometric titration method for estimation of maleic anhydride content in high molecular weight styrene maleic anhydride copolymer was developed. The method involves reaction of maleic anhydride with aniline to convert anhydride to monoacid, which was then titrated with an organic base namely alcoholic tetra-butylammonium hydroxide (TBAOH). The misperception over end-point detection by color indicators was circumvented in this method by potentiometric end-point detection. The method is accurate, repeatable and easy to implement. Highlights: A potentiometric titration method has been developed for estimating MA content in high molecular weight SMA copolymer. It involves conversion of MA into monoacid which was then titrated with organic base like alcoholic tetra-butylammonium hydroxide (TBAOH). The method comprises potentiometric end point, misperception over end point detection color indicators based methods have been circumvented.